2003
DOI: 10.1126/science.1076979
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring MAP Kinase Pathways Using Alternative Scaffold Assembly Mechanisms

Abstract: How scaffold proteins control information flow in signaling pathways is poorly understood: Do they simply tether components, or do they precisely orient and activate them? We found that the yeast mitogen-activated protein (MAP) kinase scaffold Ste5 is tolerant to major stereochemical perturbations; heterologous protein interactions could functionally replace native kinase recruitment interactions, indicating that simple tethering is largely sufficient for scaffold-mediated signaling. Moreover, by engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
269
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(279 citation statements)
references
References 26 publications
6
269
1
3
Order By: Relevance
“…In the few examples studied to date, the localization of receptors to a signaling complex is often more important than their specific orientation within the complex. [233,236] Consistent with this view, the ability of dimeric ligands to activate signaling via ZAP-70 highlights that different RE orientations often give rise to only subtle effects. [107] ZAP-70 is a kinase whose function is required for the varied signaling functions of the T cell.…”
Section: 2a G-protein Coupledmentioning
confidence: 73%
See 1 more Smart Citation
“…In the few examples studied to date, the localization of receptors to a signaling complex is often more important than their specific orientation within the complex. [233,236] Consistent with this view, the ability of dimeric ligands to activate signaling via ZAP-70 highlights that different RE orientations often give rise to only subtle effects. [107] ZAP-70 is a kinase whose function is required for the varied signaling functions of the T cell.…”
Section: 2a G-protein Coupledmentioning
confidence: 73%
“…Interestingly, these findings are consistent with studies in which fusion proteins have been used to test whether different assemblies of signaling domains influence output. [233,236] As with the ZAP-70 investigations, the orientation of different signaling domains was much less important than their recruitment to a signaling complex. It will be interesting to explore further the generality of these findings.…”
Section: 2a G-protein Coupledmentioning
confidence: 98%
“…In S. cerevisiae, Ste5p is a well-characterized scaffold protein that tethers multiple protein kinases in the mitogen-activated protein (MAP) kinase cascade required for mating and Pbs2 is involved in osmo-regulatory pathway. By creating a chimera scaffold with Ste5 and Pbs2, Park et al have redesigned yeast mitogen-activated protein kinase (MAPK) pathways that were able to generate mating responses when stimulated with high salt (Park et al, 2003).…”
Section: Synthetic Proteinsmentioning
confidence: 99%
“…To illustrate this approach, we first approximate the integrand (27) using a r − 1th order Lagrange polynomial at a set of interpolation points t n+1 , t n ,…, t n+2−r : (28) Then (12) becomes (29) A first order implicit approximation to (τ) of the form (30) leads to a first order implicit scheme (31) A second order implicit approximation to (τ), (32) leads to a second order implicit scheme (33) Like the implicit ETD methods based on the non-compact representation, the nonlinear function of U n+1 in the compact implicit ETD (33) is also multiplied by terms involving the approximated differential operators and their exponentials. This non-local coupling makes the implicit ETD method inefficient.…”
Section: Two-dimensionsmentioning
confidence: 99%
“…Scaffold usually binds dynamically to two or more consecutively-acting components of a signaling cascade. Experimental work suggests that scaffolds may promote signal transmission by tethering consecutively acting kinases near each other [31,32]. However, it has also been experimentally observed that some scaffold inhibit signaling when over-expressed [33][34][35].…”
Section: 22mentioning
confidence: 99%